Advanced Oxidation Process for DNAN Using UV/H2O2. (October 2019) - Su, Hailei; Christodoulatos, Christos; Smolinski, Benjamin; Arienti, Per; O'Connor, Greg; Meng, Xiaoguang
Abstract: 2, 4-Dinitroanisole (DNAN) is an important component of insensitive munitions that is anticipated to replace 2, 4, 6-trinitrotoluene (TNT) in munitions formulations. Photocatalyzed hydrogen peroxide (H2 O2 ) oxidation experiments and chemical analyses were conducted to study the effect of initial pH and H2 O2 dosage on the kinetics of DNAN decomposition and the reaction pathways. The results show that DNAN degradation followed zero-order kinetics when a 250 ppm DNAN solution was treated with ultraviolet (UV) light and 1500–4500 ppm H2 O2 in an initial pH range of 4–7. However, when the H2 O2 concentration was 750 ppm, DNAN degradation followed pseudo-first-order kinetics. The results indicate that DNAN can easily be oxidized by UV/H2 O2 treatment. When the H2 O2 dosage was 1500 ppm and the initial pH was 7, DNAN was reduced from 250 ppm to less than 1 ppm in 3 h. However, the total organic carbon (TOC) and total carbon (TC) concentrations were reduced slowly from 100 to less than 70 ppm carbon (C) in 3 h, and decreased to about 5 ppm after 9 h of treatment, suggesting the formation of other organic compounds. Those reaction intermediates were oxidized to carbon dioxide (CO2 ) at a slower rate than the oxidation of DNAN. CO2 was emitted from the solution because the solution pH decreased rapidly to about 3 during the UV/H2 O2 oxidation. Most of the nitrogen in DNAN was converted to nitrate by UV/H2 O2 oxidation after 9 h of treatment. The research results indicate that UV/H2 O2 oxidation is a promising technique for the treatment of DNAN in wastewater.